A SEMIOTIC ANALYSIS OF PUBLIC SERVICE ADVERTISEMENTS - Ni Made Sri Wahyuni; I Komang Sulatra; Desak Putu Eka Pratiwi (ID Solutions, 2022)
This study aimed to find out and to describe the meaning of the verbal and visual signs in public service advertisements. The data were taken from the internet, which have included the verbal and visual signs. There were two theories applied in this study. The theory of Semiotics proposed by Saussure (1983) and the theory of meaning by Leech (1981). The process of collecting data was observation method. Through the analysis it was found that verbal and visual signs have important rules to make attractive and good advertisement. In term of verbal sign, these advertisements consist of the text which has an excellent word choice to attract the reader’s interests. Meanwhile, from the visual sign, these advertisements represent unique picture which is to support verbal sign in order to make it easier for reader to understand the context of an advertisement. Overall, the use of verbal and visual sign in the advertisement is really important to share the message of the advertisement and also to attract the readers’ attention.